Characterization of watermelon juice concentrated by reverse osmosis process. - GOMES, F. S. (2009)
Watermelon is a tropical fruit with excellent flavour, color, sweetness and succulence. Nowadays it is pointed out as an excellent source of lycopene, a carotenoid with antioxidant property. The objective of this work was to concentrate watermelon juice by reverse osmosis to obtain a concentrated product rich in lycopene. The juice was obtained by the depulping the fruits in a finisher with a 0.8 mm. Reverse osmosis was carried out in a pilot plant unit with composite membranes (conditioned in a plate and frame module. totalizing a permeate area of 0.72m2. The process was carried out at 30ºC, 60 bar and 650 L/h flow rate. Samples Lycopene content was determined by extraction with hexane measured in spectrophotometer at 503 nm. Antioxidant capacity s was evaluated by extraction with hexane followed by the quantification using ABTS as radical and Trolox as standard. The color loss was determined in spectrophotometer at 734nm after 15 min of reaction of the sample with the ABTS. The mean permeate flux was 22L1h1m.